Digital inclusive finance, R&D investment, and green technology innovation nexus. - Hongying Sun; Yipei Luo; Jia Liu; Miraj Ahmed Bhuiyan (PLoS ONE)
Green technology innovation is an effective means to achieve high-quality economic development. The impact and mechanism of digital financial inclusion on regional green technology innovation are tested using a threshold regression model and the panel fixed effect model, based on China's provincial Panel data (provincial Panel data are regional annual report data) from 2011 to 2020. According to the study, there is a direct link between local green technology innovation and digital financial inclusion. This paper highlights the differences in their influence by location and usage depth and underscores the necessity of government engagement to improve these characteristics. Information infrastructure needs to be strengthened, especially in areas with gaps. Greater investment in research and development (R&D) indirectly supports regional green technology innovation since it is impacted by digital financial inclusion. Interestingly, a threshold effect becomes most noticeable when digital financial inclusion rises above a particular threshold. Promoting utilizing digital financial inclusion to lessen regional differences in green technology innovation is important.